A comparative study of intravenous patient - controlled analgesia morphine and tramadol in patients undergoing major operation - Mohamed, Rozilah @ Abdul Hadi; Hassan, Shamsulkamaruljan; Ali, Saedah; Nik Mohamed, Nik Abdullah (Malaysian Medical Associations, 2006)
The success of major surgery depends partly on providing effective post-operative pain relief, which can be commonly achieved by morphine administration via patient- controlled analgesic (PCA) system. Alternatively, tramadol which is a weak opioid analgesic, can be used for post operative pain relief. The purpose of this study was to evaluate the effectiveness of intravenous PCA tramadol in comparison with PCA morphine in term of analgesic properties, sedation and side effects. A randomized, double-blinded study was conducted on 160 ASA I and II patients who underwent major operations. 80 of them received a loading dose of intravenous morphine 0.1 mg/kg followed by PCA morphine bolus of 1 mg (1 mg/ml) as required, while the other 80 patients received a loading dose of 2.5 mg/kg of intravenous tramadol followed by PCA infusion of 10 mg (10 mg/ml) as required. Patients were monitored for pain, sedation and side effects as well as respiratory rate, nausea, vomiting, pruritus, blood pressure and pulse rate. Patients were evaluated 30 minutes, 4 hours, 24 hours and 48 hours post operation. There were no differences in the demographic data between the two groups (p>0.05). The overall mean pain score in tramadol group was 0.70  0.60 as compared to 0.75  0.67 for morphine group. The mean pain score for tramadol and morphine groups at 30 minutes, 4 hours, 24 hours and 48 hours post operation were 1.32  0.79, 1.04  0.79, 0.35  0.48, 0.09  0.33 and 1.35  0.99, 1.14  0.81, 0.40  0.54, 0.10  0.34 respectively. The overall mean sedation score in tramadol and morphine group was 0.39  0.44 as compared to 0.35  0.43 for morphine group. The mean sedation score for tramadol and morphine group at 30 minutes, 4 hours, 24 hours and 48 hours post operation were 0.90  0.74, 0.56  0.59, 0.075  0.27, 0.025  0.16 and 0.84  0.70, 0.46  0.64, 0.08  0.27, 0.01  0.11 respectively. There was no significant difference in the overall mean pain and sedation score between the two groups as well as for each duration assessed (p>0.05). There were also no significant differences between the two groups with regard to the blood pressure and heart rate. The incidence of nausea, vomiting and pruritus were the same in the two groups. This study indicates that PCA tramadol is as equally effective as PCA morphine for pain control following major surgery. The incidences of sedation, nausea or pruritus were the same in the two groups.